2013
DOI: 10.1016/j.jcdr.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile severe mitral stenosis predisposing Eisenmenger syndrome in a case with ventricular septal defect, patent ductus arteriosus, coarctation of aorta & hypoplastic aortic arch: Report of first case of rare association

Abstract: We are reporting the first case of rare association between multiple congenital cardiac malformations with severe rheumatic mitral stenosis which is an acquired structural cardiac disease. A 16 years old female patient presented with progressive dyspnoea & cyanosis for the last one month with past history of recurrent pneumonia since infancy. Physical examination revealed presence of cyanosis, grade I clubbing, radio-radial & radio-femoral delay, loud & single second heart sound, apical long mid diastolic murm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…[8][9][10] Association of RHD with PDA is more uncommon and found only in a few case reports. 11,12 Association of multiple conditions such as, RHD with TOF and PDA with PLSVC was not found before in available literature by this group of researchers, and this may be the index case of such a combination of features.…”
Section: Discussionmentioning
confidence: 79%
“…[8][9][10] Association of RHD with PDA is more uncommon and found only in a few case reports. 11,12 Association of multiple conditions such as, RHD with TOF and PDA with PLSVC was not found before in available literature by this group of researchers, and this may be the index case of such a combination of features.…”
Section: Discussionmentioning
confidence: 79%
“…following a BMV). Patra et al reported a case with rheumatic MS, large PDA, multiple VSDs, and Eisenmneger's syndrome in which the authors contemplated performing a BMV to decrease PA pressure and thus the right to left shunt [3]. However, the procedure could not be performed due to lack of consent by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Among shunt lesions, atrial septal defects (ASD) are more commonly associated with RHD, while post-tricuspid shunts such as patent ductus arteriosus (PDA) and ventricular septal defects (VSD) are relatively uncommon. Previous associations of rheumatic mitral stenosis (MS) with PDA have invariably been in the setting of a large defect with anecdotal reports of surgical closure of the PDA being reported [1][2][3]. The physiologic and clinical consequences of such an association are essentially governed by the underlying pulmonary vascular resistance which chiefly depends on the size of the PDA and severity of MS.…”
Section: Introductionmentioning
confidence: 99%